2020
DOI: 10.1371/journal.pone.0227673
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-related changes towards normalization of the abnormal external signal processing in panic disorder

Abstract: Despite the scientific consensus on the efficacy of psychotherapy for the treatment of psychological disorders, the evidence of treatment-related changes towards normalization of abnormal brain functions in patients is mixed. In the present experiment, we investigated whether treatment can affect early information processing, by testing abnormal eventrelated potentials (ERPs) evoked by internal and external signals in panic disorder. Sixteen patients with panic disorder and comorbid personality disorder and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The results revealed that the VPP evoked by feedback signals in the response-choice task and by pictures in the passive viewing task was larger in PD patients than controls 23 and that 1 year of psychotherapy resulted in a significant normalization of this abnormal response. 24 An enhanced VPP in PD patients conforms well to the hypothesis that fear might determine hypervigilance, resulting in enhanced processing of the external world. However, in depression, the tendency towards the mental world might distract from the accurate processing of the external world, resulting in a significant reduction of the VPP evoked by visual stimuli.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The results revealed that the VPP evoked by feedback signals in the response-choice task and by pictures in the passive viewing task was larger in PD patients than controls 23 and that 1 year of psychotherapy resulted in a significant normalization of this abnormal response. 24 An enhanced VPP in PD patients conforms well to the hypothesis that fear might determine hypervigilance, resulting in enhanced processing of the external world. However, in depression, the tendency towards the mental world might distract from the accurate processing of the external world, resulting in a significant reduction of the VPP evoked by visual stimuli.…”
Section: Introductionsupporting
confidence: 77%
“…Importantly, in a recent study on PD patients after 1 year of psychotherapy, Valt and collaborators showed that the VPP is sensitive to treatment-induced changes in visual processing. 24 The sensitivity of the VPP to functional normalizations induced by treatment might offer a potential tool for tracking the signs of progress also in MDD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valt et al [134] investigated a related internalizing disorder, panic disorder, and, consistent with prior literature, found that compared to controls, untreated participants had a greater ERN and also a greater vertex positive potential. In a subsequent treatment study, Valt et al [135] found that, as before, the ERN did not normalize in response to psychological treatment, but treatment-related normalization of the vertex positive potential was observed.…”
Section: Observationmentioning
confidence: 83%
“…Valt, et al [100] investigated a related internalizing disorder, panic disorder, and consistent with prior literature found that compared to controls untreated participants had a greater ERN and also a greater vertex positive potential. In a subsequent treatment study, Valt, et al [101] found that as before the ERN did not normalize in response to psychological treatment, but treatment related normalization of the vertex positive potential was observed.…”
Section: Observationmentioning
confidence: 94%